Molecular regulation and clinical significance of caveolin‐1 methylation in chronic lung diseases - Furong Yan; Lili Su; Xiaoyang Chen; Xiangdong Wang; Hongzhi Gao; Yiming Zeng (Clinical and Translational Medicine, 2020)
Abstract Chronic lung diseases represent a largely global burden whose pathogenesis remains largely unknown. Research increasingly suggests that epigenetic modifications, especially DNA methylation, play a mechanistic role in chronic lung diseases. DNA methylation can affect gene expression and induce various diseases. Of the caveolae in plasma membrane of cell, caveolin‐1 (Cav‐1) is a crucial structural constituent involved in many important life activities. With the increasingly advanced progress of genome‐wide methylation sequencing technologies, the important impact of Cav‐1 DNA methylation has been discovered. The present review overviews the biological characters, functions, and structure of Cav‐1; epigenetic modifications of Cav‐1 in health and disease; expression and regulation of Cav‐1 DNA methylation in the respiratory system and its significance; as well as clinical potential as disease‐specific biomarker and targets for early diagnosis and therapy.